Students Attitude Towards Writing Communication Skills - Yuliana, Ikka (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to know students’ attitudes towards written communication skills in English learning, in the scope of cognitive, affective, and behavioral aspects. This research used descriptive quantitative in the form of the cross-sectional survey design using a questionnaire at one point in time. The population of this study was 200 students who had taken an English course in the second semester, and the sample was 135 students (67.5%), specified by the Slovin formula. The sample of this research was chosen by probability sampling with random. The data were analyzed descriptively using the data presentation method, cross-tabulation, drawing conclusions, and T-score with the SPSS program.Based on the research, the students’ attitudes regarding cognitive, affective dan behavioral aspects towards written communication skills in English learning showed that the students have a positive attitude in improving English writing skills. Many of them feel that English writing skills need to support their learning and quite relevant to the competence of education in agriculture and beneficial and valuable for them. Self-assignment for students that must be carried out outside of face-to-face hours is also the key to improve their writing skills. Therefore, the form and substance of self-assignment should be designed by lecturers in order to make students able to write English substance well. Students need to appreciate the fact that English is very beneficial for them, not only during their studies or when completing final assignments, but beyond that, it would also be valuable after they graduated from college. Keywords: Students, Attitudes